Seroepidemiology of paratuberculosis in cattle population of organized and unorganized farms of India - NARNAWARE, SHIRISH DADARAO; TRIPATHI, BHUPENDRA NATH (The Indian Journal of Animal Sciences, 2017)
Serum samples (531) collected randomly from cattle of organized (200) and unorganized (331) farms of Central and Northern parts of India were subjected to a commercial ELISA to know the seroprevalence of paratuberculosis. These serum samples were also tested by an in-house absorbed ELISA developed in the laboratory and the results were compared. The overall seroprevalence of paratuberculosis in cattle was 8.09% with significantly higher prevalence in cattle of organized farms (13.5%) than unorganized farms (4.83%). The seroprevalence was also significantly higher in calves (17.24%) than adults (7.57%); whereas there was no significant difference in prevalence rate among male (6.71%) and female (9.87%) cattle. Region wise the seroprevalence was slightly higher in organized farms of Northern India (16.43%) than that of Central India (11.81%). The sensitivity and specificity of in-house ELISA were 71.11% and 98.76%, respectively, with the accuracy of over 96%. On the basis of Kappa-test, the inhouse ELISA was in good agreement with commercial Pourquier ® ELISA and can be recommended for screening of paratuberculosis infection in cattle in India.